Effects of Planting Media and Banana Waste-Based Liquid Organic Fertilizer on Growth and Yield of Biru Lancor Shallot (Allium ascalonicum L.) Variety - Sa'diah, Trisna Aminatus; Moeljani, Ida Retno; Suryandika, Fadila (Journal of Applied Plant Technology, 2025)
Shallots (Allium ascalonicum L.) are a high-value horticultural commodity with increasing demand, but their production is hampered by shrinking land and excessive use of inorganic fertilizers. Research is needed to find sustainable solutions for yield improvement. This study aimed to determine the most optimal planting media composition and banana tree waste POC (organic liquid fertilizer) concentration for shallot (Allium ascalonicum L.) growth. The study was conducted from July to September 2024 in Sidomukti Village, Bungah District, Gresik Regency. The method applied was a factorial experiment with a Randomized Block Design (RBD) consisting of two factors, with each treatment repeated three times, totaling 36 plants with three samples for each treatment combination. Data analysis utilized analysis of variance (ANOVA), followed by an HSD test at a 5% significance level if ANOVA showed significant results. The study revealed a significant interaction regarding plant height at 42 days after planting (DAP) and shoot dry weight. The planting media composition of soil + vermicompost + goat manure (1:2:2) significantly affected plant height at 56 DAP. A POC concentration of 30% significantly influenced the number of leaves from 21 DAP to 35 DAP.